Activist Media and Biopolitics - Wolfgang Sützl, Theo Hug (dir.) (innsbruck university press, 2012)
After tactical media became less important, many media activist projects repositioned themselves: in the context of biopolitics they challenge the hegemony of biopower. This volume contains theoretical and empirical contributions to a conference on issues of media activism and biopolitics which has been organized by Innsbruck Media Studies in 2010. Theorists and activists describe and analyze media, whose goal is to enable resistance against regimes of biopower. The control of mobility and v...